Studi Living Qur’an Terhadap Dzikir Asma’ul Husna di MAajelis Ta’lim At-Tadzkir Palembang - Kurnia Illahi; Pathur Rahman; RA Erika Septiana (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2023)
This article was inspired by the special way that the congregation did in practicing the dhikr of Asmaul Husna. This study aims to determine the effect of the dhikr of Asmaul Huna for the congregation of the At-Tadzkir Ta'lim Council, as well as the understanding of the congregation of the dhikr. At the same time, to find out the features contained in the dhikr of Asmaul Husna, so that the assembly members are motivated to practice it. This type of research is field research. Sources of data used are primary data sources and secondary data. Primary data are interviews with active worshipers in weekly studies at the at-tadzkir ta'lim assembly. As for secondary data, namely supporting primary data literature, this data relates to other parties or sources such as books, magazines, journals, articles, theses, internet, and research results. Furthermore, the data were analyzed using a qualitative descriptive method.Based on the results of the study, it can be concluded that the dhikr of Asmaul Husna can provide changes for those who practice it. Dhikr Asmaul Husna has been around for a long time, but not many people practice it directly. Therefore, the congregation of the at-tadzkir ta'lim assemblies practice it and tend to never leave it to get the virtue and blessing of the dhikr.